Two Sided of TikTok: Considering Both Positive and Negative Sides of Social Media for Language Learning - Niswatin Nurul Hidayati (Institut Agama Islam Al-Hikmah Tuban, 2022)
The presence of technology and the development of the world of social media have two inseparable sides, including positive and negative sides. One of the media favored by children and adolescents is TikTok. The purpose of this study is to discuss the two positive and negative sides of TikTok with specifications on language learning, both Indonesian as the mother language and English as a foreign language. The method used is a qualitative method with two types of data sources, namely primary and secondary data. Primary data is based on the author’s observations on the application, as well as secondary data from various written references, especially scientific articles published in journals. The results show that TikTok has positive sides, for example increasing and fostering children’s creativity, increasing the vocabulary of children and adolescents in both Indonesian and English, and so on. However, on the other hand, there is quite a lot of content posted on TikTok that features swear words. This needs to be a concern for parents to pay attention to the content opened by children.